FORMATION OF SPIRITUAL AND MORAL VALUES IN YOUNG PEOPLE THROUGH THE DEVELOPMENT OF READING CULTURE - Ravil Ramzaevich Ashrapov (Scholar Express Journal, 2025)
In this article, the author examines the processes of forming spiritual and moral values in young people through the development of a reading culture. The relevance of the topic is due to the need to strengthen moral guidelines in the conditions of modern society, characterized by rapid changes and global challenges. Key aspects of reading culture are described, such as the choice of literature, participation in reading aloud and the organization of clubs of interest. The findings indicate that the development of a reading culture plays an important role in the formation of stable spiritual and moral values, which, in turn, contributes to social harmony and cultural identity.
Keywords: Spirituality; morality; culture; youth